1-(4-Methoxyphenyl)ethane-1,2-diyl 1,1′-biphenyl-2,2′-dicarboxylate - Fun, Hoong-Kun (International Union of Crystallography, 2012)
In the title molecule, C(23)H(18)O(5), the methoxy-substituted benzene ring makes dihedral angles of 65.12 (4) and 88.55 (4)° with the other two benzene rings. These two benzene rings form a dihedral angle of 45.70 (4)°. In the crystal, molecules are linked into inversion dimers by pairs of weak C—H⋯O hydrogen bonds.